Changes in fermentation and biohydrogenation intermediates in continuous cultures fed low and high levels of fat with increasing rates of starch degradability - Lascano, Gustavo J.; Alende, Mariano; Koch, L.E.; Jenkins, Thomas C. (American Dairy Science Association, 2019)
Excessive levels of starch in diets for lactating dairy cattle is a known risk factor for milk fat depression, but little is known about how this risk is affected by differences in rates of starch degradability (Kd) in the rumen. The objective of this study was to compare accumulation of biohydrogenation intermediates causing milk fat depression, including conjugated linoleic acid (CLA), when corn with low or high Kd were fed to continuous cultures. Diets contained (dry matter basis) 50% forage (alfalfa pellets and grass hay) and 50% concentrate, with either no added fat (LF) or 3.3% added soybean oil (HF). Within both the LF and HF diets, 3 starch degradability treatments were obtained by varying the ratio of processed (heat and pressure treatments) and unprocessed corn sources, giving a total of 6 dietary treatments. Each diet was fed to dual-flow continuous fermenters 3 times a day at 0800, 1600, and 2400 h. Diets were fed for four 10-d periods, with 7 d for adaptation and 3 d for sample collection. Orthogonal contrasts were used in the GLIMMIX procedure of SAS to test the effects of fat, starch degradability, and their interaction. Acetate and acetate:propionate were lower for HF than for LF but daily production of trans-10 18:1 and trans-10,cis-12 CLA were higher for HF than for LF. Increasing starch Kd from low to high increased culture pH, acetate, and valerate but decreased butyrate and isobutyrate. Changes in biohydrogenation intermediates (expressed as % of total isomers) from low to high starch Kd included reductions in trans-11 18:1 and cis-9,trans-11 CLA but increases in trans-10 18:1 and trans-10,cis-12 CLA. The results show that increasing the starch Kd in continuous cultures while holding starch level constant causes elevation of biohydrogenation intermediates linked to milk fat depression.